2004
DOI: 10.1159/000078849
|View full text |Cite
|
Sign up to set email alerts
|

Language Acquisition in Relation to Cumulative Posttraumatic Stress Disorder Symptom Load over Time in a Sample of Resettled Refugees

Abstract: Objective: To study the effects of symptoms of posttraumatic stress disorder (PTSD), depression and dissociation as well as cumulative symptom load on language learning during the introduction phase in resettled refugees. Method: Participants were resettled refugees of Iraqi origin. They were assessed by means of a structured interview for PTSD at baseline as well as self-rating questionnaires. Language acquisition was studied by means of register data from the school system. Five levels of language proficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 17 publications
3
35
0
2
Order By: Relevance
“…Social integration in the country of resettlement can be stressful, and PTSD can further hinder language acquisition [89], cause social isolation [90] and increase acculturation stress [91]. A positive association was found between mental health symptoms and acculturation stress in both immigrants and refugees [92-94].…”
Section: Introductionmentioning
confidence: 99%
“…Social integration in the country of resettlement can be stressful, and PTSD can further hinder language acquisition [89], cause social isolation [90] and increase acculturation stress [91]. A positive association was found between mental health symptoms and acculturation stress in both immigrants and refugees [92-94].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological assessment studies in war-related PTSD have mainly been done on US veteran samples, with only few studies presenting data from different cultural groups (e.g., Gil, Calev, Greenberg, Kugelmass, & Lerer, 1990;Kivling-Boden & Sundbom, 2003;Söndergaard & Theorell, 2004). In the present study, we focus on the effects of exposure to political violence on the cognitive functioning of a civilian non-combatant sample, using an empirically validated EF model, in an attempt to both replicate previous findings and to shed further light on the clinical significance of executive impairment in PTSD.…”
mentioning
confidence: 99%
“…[38][39][40][41] Studies with refugees have identified a relationship between depressive symptomatology and cognitive impairment that makes the acculturation process difficult. [42][43][44][45][46][47][48] High-risk behaviors have also been associated with the dissolution of family support networks, homelessness, long-term unemployment and poverty. [49][50][51][52] We found that women's reduced access to social capital resources, including their social networks, may have played a role in their engagement in unsafe behaviors.…”
Section: Discussionmentioning
confidence: 99%